PERBANDINGAN PERLINDUNGAN TERHADAP ANAK KORBAN SEX TRAFFICKING DI INDONESIA DAN FILIPINA - Hermanto, Valentine Querubin; bangun, budi hermawan; itasari, endah rantau (Faculty of Law, Universitas Tanjungpura, 2023)
AbstractThis research aims to examine the comparison of the protection of sex trafficking child victims in Indonesia and in the Philippines through a legal review according to the Optional Protocol to the Convention on the Rights of the Child on the Sale of Children, Child Prostitution and Child Pornography (OPSC). The research method used is normative juridical research. The sources of legal materials used are primary, secondary and tertiary data to strengthen the analysis in terms of the norms that apply in both countries. The author is interested in examining this legal comparison due to the difference in the number of cases of sex trafficking that occur in both countries, whereas the Philippines has experienced a decrease in the number of cases and Indonesia is vice versa. The cases examined in this research revolved around the development of cases during the post-COVID 19 period or after the pandemic, due to the increasing number of human trafficking that occurred in the aforesaid period. The Philippines and Indonesia are the two countries in ASEAN region, both countries have more or less similar culture and legal system. Therefore, a comparison of laws can be made to analyze the differences in protection. AbstrakPenulisan ini bertujuan untuk mengkaji perbandingan perlindungan anak korban Sex Trafficking di Indonesia dan di Filipina melalui peninjauan menurut Optional Protocol to the Convention on the Rights of the Child on the Sale of Children, Child Prostitution and Child Pornography. Metode penelitian yang digunakan adalah penelitian hukum yuridis normatif. Sumber bahan hukum yang digunakan adalah bahan hukum primer, sekunder dan data penunjang untuk memperkuat analisa dalam segi norma yang berlaku dalam kedua negara. Penulis tertarik untuk meneliti perbandingan hukum ini dikarenakan oleh perbedaan angka kasus Sex Trafficking yang terjadi di kedua negara, dimana Filipina mengalami penurunan angka kasus dan Indonesia mengalami kenaikan dalam hal yang sama. Kasus yang diteliti dalam penelitian ini berkisar dalam perkembangan kasus selama masa post-COVID 19 atau setelah pandemi, dikarenakan melonjaknya angka perdagangan manusia yang terjadi selama periode tersebut. Mengenal Filipina dan Indonesia sebagai kedua negara yang berada dalam kawasan ASEAN dan memiliki budaya serta sistem hukum yang kurang lebih sama, perbandingan hukum dapat dilakukan untuk menganalisa perbedaan perlindungan tersebut.